PUNISHMENT OF ATTEMPT IN EU “CRIMINAL” INSTRUMENTS (EU and comparative law issues and challenges series (ECLIC), 2019)
Taking into account the continuous changes regarding the definition of attempt, a “magic formula” for distinguishing preparatory actions from attempts has not been found yet. Some suggest looking at the matter from objective observer’s standpoint, considering the circumstances the third party must be aware of, as well as the existing causal line. The objective observer fiction is the main point in the observation mode of attempt. This thesis can be applied by analysing two stages to “filter” the actions that represent attempt. In the first stage, it is necessary to decide whether and which prohibited activities may possibly be the result of a criminal offence attainment (in abstracto). In the second stage, it is necessary to ascertain whether these activities really are true, and if they are, whether or not they have reached the beginning of attempt by the CC, taking into account the perpetrator’s plan (in concreto). If a criminal offence cannot be completed, either due to natural or legal circumstances, we are referring to impossible attempt. With impossible attempt, a perpetrator needs to believe that he or she can complete a criminal offence. There are different types of impossibility, like attempt on impossible object, attempt with impossible means and double impossibility. This paper also analyses gross lack of understanding, imaginary offence and supernatural attempt as important institutes for impossible attempt. Punishment of these types of attempts is analysed in European Union instrument in the field of criminal law and related texts.